CONFERENCING APPROACH IN PROMOTING WRITING ABILITIY: A CLASSROOM ACTION RESEARCH STUDY ON LANGUAGE CREATIVE WRITING IN INDONESIAN LANGUAGE - Hartati, Tatat (Universitas Pendidikan Indonesia, 2017)
In recent days there is a growing interest in the study of creative writing. A number of approaches for teaching creative writing have also been investigated. However, studies investigating creative writing particularly for primary school students are hardly to find. The aim of the present research is to figure out how conferencing approach is applied to teach poetry writing and to find out the impact of this approach to the students’ writing skills. The study used a classroom action research with 30 sixth-grade students as the participants. To ensure the present approach effectively improves the learning achievement, the study used three cycles of teaching steps, including classical, group, and individual. Various media and sources to support the learning activities were also used. The results of the study show that there is a significant improvement in students’ writing skills, in which the average score of the third cycle was twice higher than that of the first cycle. This suggests that conferencing instruction had been successful in improving students’ writing skills. The process of interaction, both among students and between students and the teachers, were also emphasized. In addition, the teachers gained an experience of assesing poetry writing analytically using four aspects: creative idea, diction, information, and imagination.